Constitutional and Legal Basis of Privatization and Denationalization of Property in the Republic of Belarus - Demichev, Dmitry Mikhailovich (Teisė, 2021)
The article examines the features of the constitutional and legal foundations of privatization and denationalization of property in the Republic of Belarus at the present stage.